Phenological, morphological and genetic characterization of local grapevine (Vitis labrusca L.) genotypes grown in the Black Sea Region in Northern Turkey - Aydemir, Birsen Çakır; Yazıcı, Kezban; Göksu, Burcu (Emirates Journal of Food and Agriculture, 2023)
Vitis labrusca has become widely naturalized in the Black Sea region of Northern Turkey. The aim of this work was to evaluate the morphological, phenological, and genetic characteristics of V. labrusca accessions grown in the Black Sea region during the last three growing seasons. Local genotypes were described according to the Organisation Internationale de la Vigne et du Vin (OIV) ampelographic descriptor, including shoot length (cm), mature leaf size, bunch length and width, berry length and width, berry weight, number of berries, Total Soluble Solids (TTS) and titratable acidity. Additionally, phenological data, including bud burst, flowering, veraison and harvest date, were recorded. The accessions were characterized at the molecular level, and genetic relationships were assessed by means of Inter Simple Sequence Repeat (ISSR) markers. Using 6 ISSR primers, seventy-seven bands were obtained, of which 69 were polymorphic with a mean polymorphic rate of 88.68%. These ISSR primers produced polymorphism information content (PIC) values ranging from 0.48 to 0.5. The genetic similarity ranged from 0.08 to 0.83 among the genotypes. According to the dendrogram based on the ISSR analysis, Accessions 8 and 5 were genetically related, with a coefficient of similarity of 0.83, while Accession 3 was the most distantly related genotype, with a coefficient of similarity of 0.08. These results demonstrated that ISSR markers can be used for genetic diversity analysis among V. labrusca genotypes. Our results also described characteristics of new V. labrusca genotypes that could be valuable for future Marker-Assisted Selection (MAS) and grapevine breeding. Key words: Diversity, foxy species, Inter-Simple Sequence Repeat markers (ISSRs), Breeding, polymorphism